Perilaku pencarian informasi otomotif oleh pelanggan Youtube channel AutonetMagz di Kota Bandung - Muhammad Daffa Hafidzan; Pawit Muhammad Yusup; Saleha Rodiah (Faculty of Communication, Padjadjaran University, 2021)
This research discusses automotive information search behavior by AutonetMagz Youtube channel subscribers. The purpose of this research is to find out the six stages of automotive information search behavior by AutonetMagz Youtube channel subscribers. The method used is qualitative research method with case study approach, data collection technique is done by conducting interviews, literature studies, observations, and documentation. This research model uses a model introduced by David Ellis in 1987 consisting of starting, chaining, browsing, differentiating, monitoring, and extracting. Informant in this study consists of 5 (five) interviewees, all five are subscribers or subscribers Youtube channel AutonetMagz for a minimum of 6 months or more. The result of this research is at the starting stage, the informants began to understand the automotive information they needed then the behavior carried out is to start looking for automotive information on Autonetmagz Youtube channel. At the chaining stage, the behavior of the informant is to look to the main source of a statetment that is accompanied by the main source when delivered by the reviewer AutonetMagz. At the stage of browsing, the behavior of the five informants is to start conducting a semi-structured search for automotive information. At the differentiating stage, the informant conducts the behavior of searching for other automotive sources of information with the same content as AutonetMagz's Youtube channel on Youtube. At the monitoring stage, informants conduct behavior that is always watching the latest videos uploaded by AutonetMagz. At the extracting stage, there is no specific behavior performed by the five informants, because this stage does not have to be done at the end but can be done at any time when the informant receives automotive information and can directly select it according to what it needs.